Organising collective responsibility: on precaution, code of conduct and understanding public debate. Keynote lecture at the first annual meeting of the Society for the Study of Nanoscience and Emerging Technologies, Seattle, 11 September 2009 - von Schomberg, Rene (2009)
"This paper makes a case for organizing collective responsibility through instruments beyond the regulatory system, such as codes of conduct and various deliberative assessment mechanisms within and outside the policy context. The paper reviews the requirements for implementing an ethics of co-responsibility with a view on the challenges current and prospective developments in the nanoscience and nanotechnologies impose on the regulatory systems of modern societies."